The effect of inspiratory muscle training on swimming performance, inspiratory muscle strength, lung function, and perceived breathlessness in elite swimmers: a randomized controlled trial. Issue 6 (November 2019) - Cunha, Marisa; Mendes, Francisca; Paciência, Inês; Rodolfo, Ana; Carneiro-Leão, Leonor; Rama, Tiago; Rufo, João; Delgado, Luís; Moreira, André
Abstract: Background: According to studies performed on terrestrial sports athletes, inspiratory muscle training (IMT) may improve athletes' performance. However, evidence of its effects in elite swimmers is lacking. Therefore, we aimed to assess the effect of 12-week IMT on swimming performance, inspiratory muscle strength, lung function, and perceived breathlessness in elite swimmers. Methods: Elite swimmers from the main FC Porto swimming team (in competitive training for a minimum period of 3 years) were invited to participate and were randomly allocated into intervention or control groups. The intervention group performed 30 inspiratory efforts, twice a day, 5 times a week, against a pressure threshold load equivalent to 50% of maximal inspiratory pressure, whereas the control group performed inspiratory efforts at the same frequency but against a 15% load. Swimming performance was assessed through time trials, converted into points according to International Swimming Federation Points Table. Outcomes were evaluated before and following the 12-week study period. Results: A total of 32 participants (22 girls) were included. The median age was 15 and 14 years old for the intervention (n = 17) and control (n = 12) groups, respectively. No differences were found in swimming performance (P = .271), inspiratory muscle strength ( P = .914), forced vital capacity ( P = .262), forced expiratory volume in 1st second ( P = .265), peak expiratory flow ( P = .270), and perceived breathlessness ( P = .568) between groups after 12 weeks of intervention. Conclusion: Twelve weeks of IMT had no effect on swimming performance, lung function, and perceived breathlessness in elite swimmers. These results may be related to swimming-specific factors and/or an applied load insufficient to achieve training overload that could induce further improvements.